2015
DOI: 10.1016/j.devcel.2015.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Cdk1 Activates Pre-mitotic Nuclear Envelope Dynein Recruitment and Apical Nuclear Migration in Neural Stem Cells

Abstract: Summary Dynein recruitment to the nuclear envelope is required for pre-mitotic nucleus-centrosome interactions in nonneuronal cells, and for apical nuclear migration in neural stem cells. In each case, dynein is recruited to the nuclear envelope (NE) specifically during G2, via two nuclear pore-mediated mechanisms involving RanBP2-BicD2 and Nup133-CENP-F. The mechanisms responsible for cell cycle control of this behavior are unknown. We now find that Cdk1 serves as a direct master controller for NE dynein recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
148
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(161 citation statements)
references
References 58 publications
13
148
0
Order By: Relevance
“…Studies in rodents have shown that this protein plays an important role in dynein-based cargo transport in neurons (32)(33)(34). Consistent with these findings, missense mutations in the human BICD2 gene are also associated with SMALED (35)(36)(37) and cortical malformations (38,39).…”
Section: Significancesupporting
confidence: 71%
“…Studies in rodents have shown that this protein plays an important role in dynein-based cargo transport in neurons (32)(33)(34). Consistent with these findings, missense mutations in the human BICD2 gene are also associated with SMALED (35)(36)(37) and cortical malformations (38,39).…”
Section: Significancesupporting
confidence: 71%
“…3B) (Bolhy et al, 2011;Splinter et al, 2010). Dynein is specifically recruited during G2, just in time for the apical aspect of interkinetic nuclear migration (Baffet et al, 2015). Occasionally, a nucleus does not complete nuclear migration to the apical surface before the onset of mitosis.…”
Section: Nuclear Migration In Developing Epitheliamentioning
confidence: 99%
“…CENP-F is sequestered in the nucleus in G2, but relocates, in a Cdk1-dependent way, to the NPCs in prophase (Baffet et a., 2015). Drug inhibition of G2-phase nuclear migration can be overcome by expression of BicD2 constitutively located to the NE by fusion to the nesprin-3 KASH domain.…”
Section: Cdk1 Controls Dynein/dynactin Recruitment To Npcsmentioning
confidence: 97%
“…This seems to be orchestrated by the G2/M phase cyclin dependent kinase, Cdk1 (Baffet et al, 2015). Inhibition of Cdk1 with drugs prevented nuclear migration and inhibited accumulation of dynein at the NE in G2.…”
Section: Cdk1 Controls Dynein/dynactin Recruitment To Npcsmentioning
confidence: 99%